Characterization of the complete chloroplast genome sequence of Elaeagnus henryi Warb. ex Diels (Elaeagnaceae). Issue 10 (3rd October 2022) - Chang, Qinxiang; Li, Yan; Chen, Xiang; Yan, Yan; Xia, Pengguo
Abstract: Elaeagnus henryi Warb. ex Diels belongs to the Elaeagnaceae. Here, we reveal the complete chloroplast genome of Elaeagnus henryi . The complete chloroplast genome is 152, 244 bp in length and contains a large single-copy (LSC) region of 82, 235 bp, a small single-copy (SSC) region of 18, 279 bp and a pair of inverted repeats (IRs) of 25, 865 bp. There are 126 genes, including 81 protein-coding, 37 transfer RNA (tRNA), and eight ribosomal RNA (rRNA) genes. The total GC content of the chloroplast genome sequence is 37.1%. The maximum-likelihood phylogenetic analysis indicated that E. henryi was sister to Elaeagnus pungens (MW145133). The result may be because the species are advanced and developed from the same ancestor.